Experimental Investigation of Heat and Fluid Flow Characteristics on Expanded Metal Mesh Roughened Solar Collector - Ayalew, Yewondwosen Gzate (Trends in Sciences, 2022)
Solar air heater is used for agricultural grain products drier, curing of industrial products and for other systems requiring low grade thermal energy. Their usefulness and quantitative energy collections has been limited. This is because of low thermal efficiency with primarily as a result of low convective heat transfer coefficient, between the absorber plate and air leading to higher plate temperature. This results greater thermal energy losses. Experimental investigation has been conducted to study heat transfer enhancement by using small diameter wire ribs on absorber plate of solar air heater duct, with the roughened wall exposed to the glazing side while the remaining 3 walls were insulated. The roughened wall has relative roughness height (e/Dh) 0.0135 - 0.0406, relative roughness pitch (p/e) 10 - 20, rib height 0.5 - 1.5 mm, expanded metal mesh (L/e) 25 - 75, Short way mesh (S/e) 15 - 45, angle of attack 45° for inclined configuration, duct aspect ratio of 12 and the air flow rate corresponds to Reynolds number between 2,000 to 18,000. It has been found that the heat transfer coefficient could be improved by a factor up to 2.2 and the friction factor had been found to increase by a factor of 1.2 times that of the smooth duct. The investigation emphasized that the secondary flow rolling along the inclined ribs is responsible for higher heat transfer rates. Thermal efficiency increased from 50.58 - 65.75 %. Finally, correlation is developed for both Nusselt number and friction factor using sigma plot software, which can be selected by the designer for a given operating condition. HIGHLIGHTS At the moment agricultural products are spoiled due to poor dryer A solar air heater with expanded metal mesh roughened solar collector is designed, manufactured and experimental test is conducted An efficient solar dryer is obtained GRAPHICAL ABSTRACT